On machinability and surface integrity in subsequent machining of additively-manufactured thick coatings: A review. (May 2020) - Zhang, Peirong; Liu, Zhanqiang; Du, Jin; Su, Guosheng; Zhang, Jingjie; Xu, Chonghai
Graphical abstract: Highlights: Surface regeneration by hybrid coating and machining process are reviewed. Challenges in sequential machining of dissimilar hard coatings are analyzed. Effects of sequential machining on surface integrity of coatings are discussed. Effects of surface integrity on service performance of coatings are discussed. Abstract: The present work identifies a research review on the machinability and surface integrity issues in subsequent machining of additively-manufactured thick coatings. The challenges in subsequent machining of coated workpiece attribute to the dissimilar properties between coating vs. substrate, and its microscopic properties. This work reviews and discusses the surface generation mechanism, microstructure, porosity, bonding strength and residual stress evolutions in subsequent machining of coated workpiece. It reports various subtractive machining technologies as finish operations to improve the surface integrity of coatings, by identifying the corresponding key traits and research gaps. Grinding is commonly used for machining ceramic coatings, while hard machining for metallic-based alloy coatings. The capability of burnishing of coatings is limited because no material is removed by this process. In addition, the influences of machining-induced surface integrity on service performance of the coated workpiece are analyzed. Lower surface roughness, refiner grain sizes, higher residual compressive stress, higher bonding strength and maximum shear stress far away from the interface induced by machining can lead to improvements of service performance of the coatings. Finally, future challenges and opportunities are presented. This paper is limited to review only the machining of coated workpiece with specific forming conditions. The hybrid process would be a promising technology to provide resistances to wear, corrosion and fatigue.